Single dose oral meloxicam for acute postoperative pain in adults - Andrew Moore, R; Derry, S; McQuay, H; Moore, M (2009)
Background: Meloxicam is a non-steroidal anti-inflammatory drug (NSAID) used mainly in treating pain associated with arthritis. The usual oral dose for osteoarthritis is 15 mg daily, but lower doses of 7.5 mg are advised in older patients. This review sought to evaluate the efficacy and safety of oral meloxicam in acute postoperative pain, using clinical studies of patients with established pain, and with outcomes measured primarily over 6 hours using standard methods. This type of study has been used for many decades to establish that drugs have analgesic properties. Objectives: To assess the efficacy of single dose oral meloxicam in acute postoperative pain, and any associated adverse events. Search strategy We searched Cochrane CENTRAL (Issue 2, 2009), MEDLINE (June 2009); EMBASE (June 2009); the Oxford Pain Relief Database. Selection criteria: Randomised, double-blind, placebo-controlled clinical trials of oral meloxicam for relief of acute postoperative pain in adults. Data collection and analysis: Two review authors independently assessed trial quality and extracted data. We planned to use area under the "pain relief versus time" curve to derive the proportion of participants with meloxicam experiencing least 50% pain relief over 4 to 6 hours, using validated equations; to use number needed to treat to benefit (NNT); the proportion of participants using rescue analgesia over a specified time period; time to use of rescue analgesia; information on adverse events and withdrawals. Main results: No studies were identified by the searches that examined oral meloxicam in patients with established postoperative pain. Authors' conclusions In the absence of evidence of efficacy, at present, for oral meloxicam in acute postoperative pain, its use in this indication is not justified. Because trials clearly demonstrating analgesic efficacy in the most basic of acute pain studies is lacking, use in other indications should be evaluated carefully. Given the large number of available drugs of this and similar classes, there is no urgent research agenda. Copyright © 2009 The Cochrane Collaboration. Published by John Wiley and Sons, Ltd.